Angular Distributions and Polarization of Fluorescence in an XUV Pump–XUV Probe Scheme - Cristian Iorga; Viorica Stancalie (Atoms)
This work provides theoretical calculations of fluorescence angular distribution and polarization within an XUV pump–XUV probe scheme designed for determining ultra-short lifetimes of highly charged heavy ions. The initial pumping leads to a non-zero alignment in the excited levels. After the probing stage, the anisotropies in angular distribution and polarization of subsequent fluorescence are significantly enhanced due to the existence of a previous alignment. Furthermore, two-photon sequential excitation from a ground state with zero angular momentum to a level with angular momentum one by two aligned linearly polarized photon beams is strictly prohibited by the selection rules and may be used as a diagnostic tool to determine beam misalignment. The present approach is based on the density matrix and statistical tensor framework. We provide the analytical form for the alignment parameters caused by successive photoexcitation either with linearly polarized photon beams, or with unpolarized photons. The analytical results can generally be used to compute angular distribution asymmetry parameters and linear polarization of subsequent fluorescence for a large array of atomic systems used in pump–probe experiments.